Enhanced performance of a bio‐based diluent with both vinyl and epoxide groups for unsaturated polyester resin applications. Issue 7 (12th December 2022) - ShangGuan, Jianan; Zheng, Yanglei; Jiang, Junyi; Li, Yong; Sun, Haoran; Xiang, Shuangfei; Zhao, Shujun; Fu, Feiya; Liu, Xiangdong
Abstract: Styrene has been widely used as a reactive diluent for a variety of commercial unsaturated polyester resins (UPRs), but suffered from high volatility. In this work, we developed a bio‐based reactive diluent, 4‐vinylguaiacol glycidyl ether (DE4VG), via an epoxidation of 4‐vinylguaiacol (4VG). Excellent miscibility and high reactivity of DE4VG were demonstrated by a series of copolymerization tests with an unsaturated polyester prepolymer (named PMSD) synthesized from maleic anhydride, 1, 3‐dihydroxypropane and succinic acid. While, significant advantages in terms of viscosity and volatility were confirmed. Additionally, DE4VG provides both vinyl and epoxide groups and the epoxide groups were cured using 4, 4‐diamino diphenylmethane (DDM) to participate the network formation of the cured PMSD/DE4VG/TBPB/DDM resin, resulting in high glass transition temperature ( T g, 195°C), residual carbon (45.5%), tensile strength (41.75 MPa), and the elongation at break (4.5%), which were all significantly surpassed the cured PMSD/St/TBPB, PMSD/St/TBPB/DDM, PMSD/DE4VG/TBPB resin. This work provided a successful demonstration to replace styrene with a bio‐based reactive diluent in UPR preparation, not only overcame the high volatility of styrene, but also enhanced material performances of the cured resin. Abstract :